Towards a Historical Ecology of Intertidal Foraging in the Mafia Archipelago: Archaeomalacology and Implications for Marine Resource Management. Issue Volume 39:Issues 2(2019) (June 2019) - Faulkner, Patrick; Harris, Matthew; Haji, Othman; Crowther, Alison; Horton, Mark C.; Boivin, Nicole L.
Understanding the timing and nature of human influence on coastal and island ecosystems is becoming a central concern in archaeological research, particularly when investigated within a historical ecology framework. Unfortunately, the coast and islands of eastern Africa have not figured significantly within this growing body of literature, but are important given their historically contingent environmental, social, and political contexts, as well as the considerable threats now posed to marine ecosystems. Here, we begin developing a longer-term understanding of past marine resource use in the Mafia Archipelago (eastern Africa), an area of high ecological importance containing the Mafia Island Marine Park. Focusing on the comparatively less researched marine invertebrates provides a means for initiating discussion on potential past marine ecosystem structure, human foraging and environmental shifts, and the implications for contemporary marine resource management. The available evidence suggests that human-environment interactions over the last 2000 years were complex and dynamic; however, these data raise more questions than answers regarding the specific drivers of changes observed in the archaeomalacological record. This is encouraging as a baseline investigation and emphasizes the need for further engagement with historical ecology by a range of cognate disciplines to enhance our understanding of these complex issues.